Bagaimana Model SETS Bekerja Melalui E-Modul untuk Meningkatkan Keterampilan Berpikir Kritis Siswa? Tingkat keefektifan bahan ajar. - Septania Pratiwi; Jaridatul Muniroh; Zuhdan Kun Prasetyo; Jumadi Jumadi; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are 21st century skills that can be improved through the use of appropriate learning models and supported by the prior knowledge that students already have. One of the learning models that can improve critical thinking skills is the SET learning model through the Science E-Module. The purpose of this study was to show the effectiveness of the application of SETS-based e-modules in Natural Science (IPA) subjects with the topic of waves and sound to improve students' critical thinking skills. This study used a quantitative descriptive design with one-group pretest-posttest technique. The sample consisted of 29 students from class VIII.C who were selected through cluster sampling. Data were analyzed using the normalized N-gain method and paired sample t-test. The results showed that the average N-gain of students' critical thinking skills after implementing learning through SETS-based science e-modules on wave and sound material was 0.4, including in the medium category. The average critical thinking skills of students after the intervention (72) were significantly higher than before the intervention (51). In addition, students' response to the SETS-based science e-module on wave and sound material resulted in a score of 90.4% which showed very good criteria. Therefore, it can be concluded that the implementation of SETS-based science on wave and sound materials can improve students' critical thinking skills.